2006
DOI: 10.1080/01904160500320962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Farmyard Manure and Inorganic Fertilizers on Sorghum Growth, Yield, and Nitrogen Use in a Semi-Arid Area of Ethiopia

Abstract: A field experiment was conducted to assess the effect of the combined use of farmyard manure and inorganic fertilizer on the growth and yield of sorghum and on soil chemical properties in a semi-arid area in northeastern Ethiopia. Twelve treatments comprising factorial combinations of four levels of farmyard manure (0, 5, 10, and 15 t ha −1 ) and three levels of inorganic fertilizers (0%, 50%, and 100% of the recommended rate) were compared in a randomized complete block design with three replications over a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
61
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 29 publications
13
61
0
2
Order By: Relevance
“…This finding is consistent with the observation of earlier researchers on the integration of organic manure with inorganic soil-applied fertilizer for okra (Akande et al 2010;Abd El-Kader et al (2010) and other crops such as maize (Makinde and Ayoola 2008), rice (Satyanarayana et al 2007), sorghum (Bayu et al 2006), and sweet maize (Uwah et al 2011). Foliar fertilizers are fast acting because the nutrients are absorbed at the site where they are readily utilized.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with the observation of earlier researchers on the integration of organic manure with inorganic soil-applied fertilizer for okra (Akande et al 2010;Abd El-Kader et al (2010) and other crops such as maize (Makinde and Ayoola 2008), rice (Satyanarayana et al 2007), sorghum (Bayu et al 2006), and sweet maize (Uwah et al 2011). Foliar fertilizers are fast acting because the nutrients are absorbed at the site where they are readily utilized.…”
Section: Discussionsupporting
confidence: 82%
“…Tolesaa and Friesen (2001) reported that the application of 25% recommended inorganic NP fertilizers + enriched FYM resulted in the highest marginal rate of return in maize indicating that the integrated approach can enable to save up to 75% of commercial fertilizers. Likewise, Bayu et al (2006) also reported the possibility of saving up to 50% of the recommended NP fertilizers due to amendment with 5-15 t ha -1 FYM to sorghum crop without significantly affecting the optimum possible yield that can be obtained with the application of full dose of inorganic NP fertilizers alone. Joy et al (2005) reported the possibility of substituting up to 25% inorganic fertilizers with the Effect of Integrated use of cattle manure and inorganic fertilizers on tuber yield of potato in ethiopia application of 30 t ha -1 FYM while still maintaining the highest rhizome yield and quality of black musli.…”
Section: Introductionmentioning
confidence: 94%
“…Lombin et al (1991) mengemukakan bahwa penggunaan pupuk organik dikombinasikan dengan pupuk anorganik merupakan strategi pengelolaan lahan kering yang dapat meningkatkan produktivitas tanah, hasil tanaman dan mengurangi dosis penggunaan pupuk anorganik. Hasil yang tinggi secara berkelanjutan dapat dicapai jika pemupukan NPK dikombinasikan dengan penggunaan bahan organik (Makinde et al, 2001;. Bayu et al, 2006).…”
Section: Pendahuluanunclassified